Assessment of compliance of wholesale pharmaceutical establishments with Good Distribution Practices (GDP) and ISO 9001:2015 standards in Kinshasa Province, Democratic Republic of the Congo - Kisangala Mfubilioni, José; Bayebila Menanzambi, Trésor; Mbinze Kindenge, Jérémie (Orapuh Journal, 2026)
Introduction Two major trends have been observed in the Democratic Republic of the Congo (DRC) over the past decades: the increasing number of licences issued to open wholesale pharmaceutical establishments and the circulation of medicines of questionable quality. These trends raise serious concerns about population health. Purpose The aim of this study was to assess compliance with Good Distribution Practices (GDP) and ISO 9001:2015 standards among wholesale pharmaceutical establishments (WPEs) operating in the Democratic Republic of the Congo. Methods This cross-sectional study was conducted from January to June 2025 in the city of Kinshasa. Twenty-five pharmaceutical depots were randomly selected from a total of 110 wholesale pharmaceutical establishments listed by ACOREP in Kinshasa Province. Data were collected using two assessment tools (one for GDP and the other for ISO 9001:2015), direct observation of infrastructure, and semi-structured interviews with managers. The collected data were analysed using the chi-squared test to assess homogeneity and heterogeneity between establishments. Results Statistical analysis revealed significant heterogeneity among the studied establishments. Of the 25 pharmaceutical warehouses assessed, the reported p-values varied according to the evaluated standards and parameters. Regarding GDP, only one parameter demonstrated homogeneity, namely the documentation system (p = 0.622). All other parameters showed significant heterogeneity: quality system (p = 0.0239), personnel (p = 0.001), medicine storage (p < 0.001), and information technology systems (p = 0.0295). For ISO 9001:2015, homogeneity was observed for leadership (p = 1), planning (p = 0.854), and performance evaluation (p = 0.638). However, heterogeneity was identified in organisational context (p < 0.001), support (p < 0.001), operational activities (p < 0.001), and continuous improvement (p = 0.0716). Conclusion Compliance with GDP and ISO 9001:2015 standards remains insufficient in the Democratic Republic of the Congo, particularly with regard to ensuring the quality and safety of medicines. Continuous auditing and inspection of wholesale pharmaceutical establishments are required nationwide, especially in Kinshasa, where more than 70% of such establishments are located. Continuing professional education on GDP and ISO standards for pharmacists and their staff must be strengthened according to a structured schedule. The role of the responsible pharmacist should also be reinforced, and warehouse owners must make substantial contributions to quality assurance efforts. The observed operational heterogeneity among wholesale pharmaceutical establishments compromises medicine quality assurance in Kinshasa. Urgent action by health authorities is required to safeguard the health security of the Congolese population.